A standardized patient education class as a vehicle to improving shared decision-making and increasing access to breast reconstruction. Issue 8 (August 2020) - Henn, Dominic; Momeni, Arash
Summary: Background: Shared decision-making is a key component of patient-centered care and has been shown to improve patient satisfaction and quality of life. Herein, we study the impact of a standardized patient education class for prospective breast reconstruction patients on clinic efficiency, access to care, and perception on shared decision-making. Methods: The number of new patient consultations per clinic, as well as average duration of the first individual clinic encounter, was compared before and after the introduction of a standardized education class given by the senior author to all new breast reconstruction patients. To evaluate patients' perception of shared decision-making, the 9-item Shared Decision-Making Questionnaire (SDM-Q9) and the Satisfaction with Information scale of the BREAST-Q Reconstruction Module were electronically distributed among the patients and compared between the two groups. Results: Introduction of the patient education class was associated with a significant reduction in the duration of new patient encounters compared to historic controls (31.8 min vs. 53.5 min, p < 0.01) along with permitting a 43% increase in new patient visits. No differences in self-perceived patient education and autonomy were seen between class participants and historic controls in the SDM-Q9 scores ( p = 0.58) and BREAST-Q scores ( p = 0.14). Conclusion: The introducing a standardized patient education class translated into a significant reduction in the duration of individual new patient encounters, thereby increasing patient access to care, while maintaining high-quality standards of self-perceived patient education and shared decision-making.